Advertisement calls, intraspecific variation and species diagnosis of six Brazilian species of Elachistocleis (Anura: Microhylidae: Gastrophryninae) - Marinho, Pedro; de Carvalho, Thiago Ribeiro; Bang, Davi Lee; Teixeira, Bernardo Franco Da Veiga; Azarak, Priscila Alencar; Campos, Carlos Eduardo Costa; Giaretta, Ariovaldo Antonio (Zootaxa, 2018)
We describe for the first time the advertisement calls of three Elachistocleis species (E. surumu, E. magna, E. carvalhoi) and provide additional data on the calls of three other species (E. matogrosso, E. helianneae, E. muiraquitan). Additionally, we evaluate intraspecific variation in morphology and color patterns, and comment on species diagnosis in the genus. The advertisement calls of the six species of Elachistocleis have a stereotyped temporal and spectral structure, which consists of a long sustained multipulsed note with an upsweep in frequency at its onset, followed by a constant frequency along the note. Newly collected Elachistocleis from northern and western Brazil showed intraspecific variation in morphology and coloration that had not been previously reported. Coloration was listed as a diagnostic feature in the original descriptions of the Elachistocleis species evaluated in this study, but color patterns were variable in some species and sometimes did not allow for species differentiation. Our results indicated that the three species with greater degrees of morphological similarity (E. helianneae, E. matogrosso, E. muiraquitan) differed in microtemporal and spectral traits of their calls. Moreover, pulse duration in E. helianneae was very distinct, lasting approximately twice the average pulse duration in calls of the other species studied. Therefore, pulse duration might be an informative trait when assigning specimens to E. helianneae, which is widely distributed across Amazonian lowland forests and in a region of Amazonian savanna. Our results bring novelties on species diagnosis and intraspecific variation in Elachistocleis based on acoustic evidence and morphological/color patterns, and accentuate the importance of taking into consideration multiple lines of evidence as a means for accurate species-level identification in this genus of Neotropical frogs.